NEGOSIASI ANTARBUDAYA DALAM KOMUNIKASI PEMERINTAH DAN KOMUNIKASI ETNIS DI MEDAN - Ratulangi, Dinda; Marzuki, Marzuki (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This study aims to analyze the practice of intercultural negotiation in communication between the government and multi-ethnic communities in the city of Medan. As the largest metropolitan city outside Java Island, Medan is home to a highly diverse population, including Batak, Malay, Javanese, Chinese, Minangkabau, and Karo ethnic groups, which presents significant challenges in the delivery of public policies. A qualitative descriptive approach was employed, using in-depth interviews, participatory observation, and document analysis as data collection techniques. The findings reveal that intercultural communication between the government and ethnic communities takes place through various channels, such as social media, face-to-face meetings, and the involvement of community leaders as cultural mediators. The main challenges identified in the communication process include language and dialect differences, cultural stereotypes, and unequal access to information. To address these challenges, the government has implemented strategies such as two-way communication, intercultural communication training for public officials, and the active involvement of community figures. Public perception of government communication varies; some ethnic groups feel adequately included, while others believe their cultural diversity is not fully accommodated. In conclusion, although efforts have been made to foster inclusive and culturally sensitive communication, further improvements are necessary to bridge cultural differences and strengthen harmonious relationships among ethnic groups in Medan.